Peran Mutu Sumberdaya Manusia PMA dan PMDN Penyerapan Tenaga Kerja di Indonesia - Hesty Nopiana Dewi; Syahrituah Siregar, SE, MA. (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research was conducted to analyze (1) whether the quality of humanresources, foreign investment, domestic investment affects employment in Indonesia; (2)what is the dominant variable influencing jobs in Indonesia. This study indicatesthat the regression analysis made shows that all dependent variables, such as thequality of the human resource, foreign investment, and domestic investment, affectIndonesia's labor absorption. Foreign investment has become the most dominantvariable. It has a significant effect on the independent variable, namely the totalworkforce on employment in Indonesia. Indonesia is still very dependent on foreigninvestment, entering Indonesia to accelerate economic growth and absorb moreworkers again in Indonesia.